Kritik Atas Pelaksanaan Asuransi Syariah Pada Pt Allianz Life Indonesia - Sobarna, Nanang; Hakim, Abdul (Jurnal Ekonomi Syariah, 2019)
This study aims to criticize the application of sharia principles at the operational level of sharia insurance companies which are conventional insurance units, namely the Allianz Life Indonesia Insurance. The study was conducted using primary data, both observations and use of records and reports owned by the company. Data obtained and analyzed by descriptive method with a qualitative approach. The results obtained from this study are that the operational mechanism of Allianz Life Indonesia's insurance in general is in accordance with Islamic principles, but it needs some further research on the tabarru of premium payments on allisya protection products, which payments begin on the 13th month, while based on national fatwas Tabarru Islamic Premium Payment is carried out since the first month of membership.